DOA SEBAGAI SARANA KOMUNIKASI DENGAN SANG PENCIPTA - Najra Nabiila Hajar (Pascasarjana IAIN Ambon, 2022)
This research is discussed to find out the importance of prayer as a means of communication with the Creator. Prayer is intended as worship to Allah SWT. Prayer is the essence of worship. This is like the hadith of the Prophet Muhammad which reads